1975
DOI: 10.1037/h0076515
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological correlates of responsiveness in schizophrenia.

Abstract: Responsiveness under stress was measured through music preferences for 11 male and 9 female schizophrenics receiving no antipsychotic medication. Results indicated that higher responsiveness was related to lower skin conductance, fewer body movements, greater diastolic blood pressure decrease, better word recall, and shorter periods of institutionalization. Normal controls did not differ significantly in music preferences but were lower in all physiological measures. Finding that sweat gland activity, muscle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…DeWolfe el al. [4] reported that reactive schizophrenics preferred relaxed music and process schizophrenics preferred tense music. Iwata [5] described that a rating of mood on semantic differentials varied con siderably between neurotic groups, especially when divided into stress and nonstress groups.…”
Section: Introductionmentioning
confidence: 99%
“…DeWolfe el al. [4] reported that reactive schizophrenics preferred relaxed music and process schizophrenics preferred tense music. Iwata [5] described that a rating of mood on semantic differentials varied con siderably between neurotic groups, especially when divided into stress and nonstress groups.…”
Section: Introductionmentioning
confidence: 99%